The Domination of the Local Party of Aceh Parliament in Responding the Aspiration of Community - Sayed Amirulkamar; Ismail Ismail (Budapest International Research and Critics University, 2019)
The Unitary State of the Republic of Indonesia as a country of island diversity, culture, ethnicity, language and others which makes Indonesia political power does not adhere to the system of any country, but adopts the existence of the order of life of the Indonesian people by combining the